French influence checked in Africa - Belaunde Matossian, Francisco (2023)
The relative loss of French influence in Africa should not be surprising in a context of competition among various powers to mark their presence on the continent. However, this phenomenon, which could be considered inevitable, is currently aggravated by the spread of a feeling of rejection of France in several of its former colonies, such as the Central African Republic, Mali and Burkina Faso. This is due to reasons attributable to France itself, as well as to the action of Russia, which, in the last few years, has shown itself to be quite enterprising in that area. Among the first, we can mention the memory of the abuses of the colonial era, as well as the period of the so-called Françafrique and certain current clumsiness; the latter basically concern the Russian propaganda and narrative widely disseminated on the continent. The French government seeks to react with some actions that can be considered wise, but it is clear that its effort will take some time to bear fruit.